Differentiating Scrub Typhus, Dengue Fever and Typhoid Fever in Indian Children Presenting with Acute Febrile Illness - Chatterjee, Saheli Misra; Mondal, Suman; Mukhopadhyay, Kaushik; Das, Niloy Kumar (Journal of Nepal Paediatric Society, 2020)
Introduction: The disease spectrum of dengue, scrub typhus and typhoid presenting as acute febrile illness is often a diagnostic dilemma to the clinician. The purpose of this study is to compare the clinical features and laboratory parameters of children suffering from typhoid, dengue and scrub typhus and use these parameters in early identification of scrub typhus before conclusion is made from serological diagnosis. Methods: A retrospective observational analytical study was conducted among children presenting with acute febrile illness in a tertiary care level hospital. Over the period of one year 113 cases were identified of which 39 were dengue, 44 were typhoid and 30 were scrub typhus. Results: The mean age of the children was 7.45 ± 2.98 years, median was eight with an interquartile range of six to ten years. The male to female ratio was 1.3:1. Symptoms of vomiting (61.54%), headache (46.15%) and hepatomegaly (47.37%) were significantly higher among children with dengue fever. A significantly higher number of children with scrub typhus fever had temperature above 40°C. The incidence of low haemoglobin, raised C reactive protein, raised ALT and low albumin levels were significantly higher in them. Children with acute febrile illness having temperature > 40°C, absolute neutrophil/lymphocyte ratio > 2 early in the illness were more likely to suffer from scrub typhus with relative probability ratio (RPR) of 25.68 and 10.57 respectively (p < 0.001). Children with WBC < 5000/mm3 were more likely to be suffering from dengue with RPR of 10.60 (p < 0.001). Conclusion: Children with acute febrile illness with temperature > 40°C and absolute neutrophil/lymphocyte ratio > 2 early in the illness were more likely to be suffering from scrub typhus.